Picky Eating Is Associated with Lower Nutrient Intakes from Children’s Home-Packed School Lunches - Gan, Kellseigh (Nutrients, 2021)
The objective was to assess the relationship between children’s picky eating (PE) status and nutrient intake from home-packed school lunches. The lunches of 321 students, aged 7–10 years, were quantified via cross-sectional direct observation. Children were classified as having PE (n = 155) or not (non-PE; n = 166) based on food neophobia scores and parental perceptions of PE. The PE group consumed significantly less protein, folate, magnesium, potassium, zinc, and vitamins B1, B2, B3, B6, D, and E than the non-PE group; however, both groups consumed amounts exceeding Dietary Reference Intakes (DRIs) for protein, carbohydrates, sugar, sodium, iron, and vitamins B1, B2, B3, B6, B12, and C. Conversely, both groups consumed amounts significantly lower than DRIs for calcium, fibre, folate, magnesium, potassium, zinc, and vitamins A, D, E, and K. The PE group ate significantly less meat and alternatives, vegetables and fruit, and fruit than the non-PE group, and did not meet any of Canada’s Food Guide (2007) recommendations. The non-PE group met recommendations for meat and alternatives only. PE impacts the dietary intake of children’s home-packed lunches; however, many packed lunches were of low nutritional quality. Focus should be placed on provision of nutritionally complete school lunches for all children.